PENINGKATAN MUTU PRODUKSI DAN PEMASARAN GULA SEMUT BERIODIUM DI KOPERASI SERBA USAHA (KSU) LIGASIREM SUMBANG-BANYUMAS - Mustaufik Mustaufik (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2014)
Banyumas is the centre of the crystal coconut sugar (Ant Sugar) producer very potensial in Central Java. In Banyumas, there are approximately 200 business units spread of “ant sugar” in the District of Cilongok and Sumbang. On the hand, Sumbang District includes areas that are endemic levels of Iodine Deficiency Disorders Diseases was quite high (39,3 percent) (Hadisaputro et al., 1997). Based on the properties and utilization, crystal coconut sugar is one product that is right for alternative food fortified with iodine. Based on this, then do devotion Program to community Service basis on result of research about application technology of production of crystal coconut sugar industry iodized in home industry coconut sugar of KSU Liga Sirem In Sikapat Village, Sumbang district, Banyumas regency. The method is done by technical assistance and learning by doing in the application of science and technology and in business management ant sugar iodized. The target outcomes of this program is the increased skill of coconut sugar home industry in producing quality ant sugar iodized in accordance with SNI and health standards as well as high economic value, there by increasing income and public health, Resulth of Program to community Service basis on result of research, among others: (1) coconut sugar home industry on KSU Liga Sirem has been able to apply the technology of production of ant sugar iodized by two methods, first methods bases raw material from “ pure nira” and second methods based raw material from coconut sugar (reproduction), (2) The product of ant sugar iodized 30 –80 ppm of KIO3 solution produced by the coconut sugar home industry KSU Liga Sirem has been in accordance with quality standards set by SNI-SII.0268-95 and Depkes RI and also having a preference that preferred by consumers, (3) Improving of quality and packaging of ant sugar product can increase the value-added products Rp. 15.000/kg to Rp.20.000/kg. (4) the program has a positive impact on increasing income and public health in home industry of crystal coconut sugar at KSU Ligasirem of Sikapat Village, Sumbang District, Banyumas Regency